Denosumab for Treatment of Hypercalcemia of Malignancy - Hu, Mimi I. (Endocrine Society, 2014)
CONTEXT: Hypercalcemia of malignancy (HCM) in patients with advanced cancer is often caused by excessive osteoclast-mediated bone resorption. Patients may not respond to or may relapse after iv bisphosphonate therapy. OBJECTIVE: We investigated whether denosumab, a potent inhibitor of osteoclast-mediated bone resorption, reduces serum calcium in patients with bisphosphonate-refractory HCM. DESIGN, SETTING, AND PARTICIPANTS: In this single-arm international study, participants had serum calcium levels corrected for albumin (CSC) >12.5 mg/dL (3.1 mmol/L) despite bisphosphonates given >7 and ≤30 days before screening. INTERVENTION: Patients received 120 mg sc denosumab on days 1, 8, 15, and 29 and then every 4 weeks. MAIN OUTCOME MEASURES: The primary endpoint was the proportion of patients with CSC ≤11.5 mg/dL (2.9 mmol/L) (response) by day 10. Secondary endpoints included response by visit, duration of response, and the proportion of patients with a complete response (CSC ≤10.8 mg/dL [2.7 mmol/L]) by day 10 and during the study. RESULTS: Patients (N = 33) had solid tumors or hematologic malignancies. By day 10, 21 patients (64%) reached CSC ≤11.5 mg/dL, and 12 patients (33%) reached CSC ≤10.8 mg/dL. During the study, 23 patients (70%) reached CSC ≤11.5 mg/dL, and 21 patients (64%) reached CSC ≤10.8 mg/dL. Estimated median response duration was 104 days. The most common serious adverse events were hypercalcemia worsening (5 patients, 15%) and dyspnea (3 patients, 9%). CONCLUSIONS: In patients with HCM despite recent iv bisphosphonate treatment, denosumab lowered serum calcium in 64% of patients within 10 days, inducing durable responses. Denosumab may offer a new treatment option for HCM.